2021
DOI: 10.1038/s41598-021-87788-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal characterization of fracture healing patterns and assessment of biomaterials by time-lapsed in vivo micro-computed tomography

Abstract: Thorough preclinical evaluation of functionalized biomaterials for treatment of large bone defects is essential prior to clinical application. Using in vivo micro-computed tomography (micro-CT) and mouse femoral defect models with different defect sizes, we were able to detect spatio-temporal healing patterns indicative of physiological and impaired healing in three defect sub-volumes and the adjacent cortex. The time-lapsed in vivo micro-CT-based approach was then applied to evaluate the bone regeneration pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…S1 ). Similar to observations from a previous femur defect study 25 , nest building started on the day of surgery and all animals were found in groups in the nest in the morning of post-operative day 1. In both groups, social interaction between mice and nesting behaviour during the pre-loading healing period (week 0–3) and the loading period (week 3–7) did not differ from pre-surgical observations.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…S1 ). Similar to observations from a previous femur defect study 25 , nest building started on the day of surgery and all animals were found in groups in the nest in the morning of post-operative day 1. In both groups, social interaction between mice and nesting behaviour during the pre-loading healing period (week 0–3) and the loading period (week 3–7) did not differ from pre-surgical observations.…”
Section: Resultssupporting
confidence: 85%
“…Compared to histology-based determination of the bone formation rate via in vivo application of fluorescent dyes (e.g. calcein, alizarin), our micro-CT-based monitoring approach with registration of consecutive scans also allows for assessment of the bone resorption rate in individual animals, which was shown to be particularly suited for the characterization of the remodelling phase during the fracture healing process 25 , 26 . The most striking loading-mediated effect in the current study was the prompt and significant reduction in bone resorption rate (week 3–4 vs. week 2–3), which was seen in the central and periosteal VOIs (DC, FP) as early as 1 week after loading (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By applying time-lapsed in vivo micro-CT and animal-specific real-time micro-finite element (RTFE) analysis, the developed femur defect loading model allows scaling of loading settings based on strain distribution in the callus 16 , thereby considering individual differences in healing speed. To follow the healing progression in each animal, a recently developed longitudinal in vivo micro-CT based approach was applied, which was previously shown to capture the different healing phases and to discriminate physiological and impaired healing patterns 17 , without significant radiation-associated effects on callus properties 18 . By registering consecutive scans of the defect region for each animal and implementing a two-threshold approach, data on bone turnover and mineralization kinetics can be obtained, which is particularly important for targeting callus remodelling under different conditions.…”
Section: Introductionmentioning
confidence: 99%